The anti‐ischemic potential of angiotensin‐converting enzyme inhibition: Insights from the heart outcomes prevention evaluation trial - Pitt, Bertram (Clin Cardiol, 2009)
Therapy with an angiotensin‐converting enzyme (ACE) inhibitor is established for reducing excessive blood pressure, reducing mortality in patients with congestive heart failure (CHF), preventing the development of CHF in patients with asymptomatic left ventricular (LV) dysfunction, and preventing death and CHF when initiated early after the onset of acute myocardial infarction (MI). Although these benefits have been attributed largely to hemodynamic mechanisms, recent preclinical and clinical evidence reveal ACE inhibition as potent in preventing ischemic events and in blocking an array of ischemic processes, including atherogenesis. A major contributor to this new evidence is the large, placebo‐controlled Heart Outcomes Prevention Evaluation (HOPE) trial, which found that the ACE inhibitor ramipril (10 mg daily) prevented MI and other ischemic events in patients with a broad range of cardiovascular (CV) risks (including coronary artery disease, stroke, peripheral vascular disease, or diabetes plus one additional risk factor) but no LV dysfunction or history of heart failure at baseline. The data from the HOPE trial suggest a greatly expanded role for ramipril in the prevention and management of CV disease.